MED16 and MED23 of Mediator are coactivators of lipopolysaccharide- and heat-shock-induced transcriptional activators - Kim, Tae Whan (National Academy of Sciences, 2004)
Transcriptional activators interact with diverse proteins and recruit transcriptional machinery to the activated promoter. Recruitment of the Mediator complex by transcriptional activators is usually the key step in transcriptional activation. However, it is unclear how Mediator recognizes different types of activator proteins. To systematically identify the subunits responsible for the signal- and activator-specific functions of Mediator in Drosophila melanogaster, each Mediator subunit was depleted by RNA interference, and its effect on transcriptional activation of endogenous as well as synthetic promoters was examined. The depletion of some Mediator gene products caused general transcriptional defects, whereas depletion of others caused defects specifically related to activation. In particular, MED16 and MED23 were required for lipopolysaccharide- and heat-shock-specific gene expression, respectively, and their activator-specific functions appeared to result from interaction with specific activators. The corequirement of MED16 for other forms of differentiation-inducing factor-induced transcription was confirmed by microarray analysis of differentiation-inducing factor (DIF)- and MED16-depleted cells individually. These results suggest that distinct Mediator subunits interact with specific activators to coordinate and transfer activator-specific signals to the transcriptional machinery.